Análisis de riesgos de liquidez en la cooperativa de ahorro y Credito Kullki Wasi Ltda - Lluashco Toalombo, Segundo Fernando (2024)
The study addressed the challenge of managing financial risks in institutions such as” Cooperativa de Ahorro y Crédito Kullki Wasi Ltda.” which face volatility in their assets and liabilities. Its main objective was to analyze the weekly percentage changes in demand and time deposits using the historical volatility method to understand the cooperative's financial evolution and management capacity. The methodology included calculating weekly percentage changes and analyzing key statistics such as standard deviation, annual volatility, and the 95% VAR multiplier. The results revealed a cumulative trend of 14.86% in demand deposits over the year, with significant fluctuations in weekly balances. Additionally, variability was observed in time deposits up to 90 days, with periods of growth followed by adjustments and fluctuations. In conclusion, the analysis provided a deep understanding of the cooperative's financial volatility, considering the importance of managing financial assets to maintain stability and liquidity in a changing environment.